The Use of E Tihamah Application to Support MA Tihamah Putra Education - Muis, Rizal Rahmawan; Suklani, Suklani; Kambali, Kambali (CV. Strata Persada Academia, 2025)
This study investigates the use of the E Tihamah application in supporting the educational management of facilities and infrastructure at MA Tihamah Putra. Educational support units play a pivotal role in ensuring the smooth operation of educational institutions, especially in managing resources and infrastructure. As the digital era advances, the optimization of educational management through technology becomes increasingly important. In this context, the E Tihamah application is introduced as an innovative solution to enhance the efficiency and accuracy of facility management, ultimately contributing to more effective educational processes. The research employs a descriptive qualitative approach to analyze the technical and operational aspects of the application and its functions. Data were collected through direct observation of the application’s features and its impact on the school’s administrative efficiency. The results highlight the significant improvements in administrative processes, communication, and decision-making transparency. Furthermore, the study explores the role of the application in supporting digital learning and fostering better interaction between teachers, students, and parents. This paper concludes that the E Tihamah application plays a key role in enhancing educational quality by streamlining management and supporting interactive, independent learning. The study recommends continuous training for stakeholders and regular updates to the application to meet evolving educational needs.